Infografi Pemerataan PBB (Pajak Bumi Bangunan) di Kantor Bapenda Kabupaten Nabire Menggunakan ArcGIS - Kristia Yuliawan; Abigael Jenifer Simopiaref (STMIK Pesat Nabire, 2026)
Geographic Information Systems (GIS) based on ArcGIS are crucial tools for analyzing and visualizing the equitable distribution of Land and Building Tax (PBB) in Nabire Regency. This research aims to design a comprehensive spatial infographic that illustrates PBB distribution and assists the Nabire Regency Revenue Agency (Bapenda) in identifying potential areas for increased revenue. Through the processing of spatial and non-spatial data, the study reveals significant imbalances in PBB collection across different regions, with urban and economic centers showing higher achievements compared to peripheral areas. The resulting thematic maps and pie diagrams effectively visualize the proportion of PBB potential versus realization, highlighting areas with untapped tax potential. These findings underscore that geospatial visualization not only aids in making fair and equitable fiscal policies but also plays a strategic role in raising public awareness and participation in PBB payments, aligning with principles of fiscal justice and optimalization of Local Own-Source Revenue (PAD).